Mathematical Model of Fluid Filtration to a Multistage Hydraulically Fractured Horizontal Well - A.B. Mazo; K.A. Potashev; M.R. Khamidullin (Учёные записки Казанского университета: Серия Физико-математические науки)
This paper presents a three-dimensional numerical model based on the finite volume method for simulation of single-phase fluid filtration towards a multistage hydraulically fractured horizontal well (MHFHW). The impact of fracture and well characteristics on the well productivity is numerically investigated. The approximation method for multistage fracturing efficiency estimation is proposed. It is based on a 3D problem simplification to a one-dimensional partial differential model due to different kinds of flow symmetry in the near well-bore area. The resulting solution of the simplified problem is improved with the help of 3D simulation. The technique can be used for rapid multistage fracturing efficiency estimation. Furthermore, it can be embedded into generic oil reservoir simulation models.